The Influence of Islamic Values Internalization on Students' Religious Character at SMA Islam Kepanjen - Yulivia Niril Suprabadinda; Saifuddin Saifuddin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This research is motivated by the importance of internalizing Islamic values in shaping the religious character of students. The internalization of Islamic values is a continuous process of instilling Islamic teachings and values through habituation, role modeling, and religious activities both within the school environment and in daily life. In the modern era, students require not only academic knowledge but also the formation of a religious character to possess good morals, discipline, responsibility, and behavior aligned with Islamic teachings. Therefore, the internalization of Islamic values plays a crucial role in developing students' religious character. The research problem in this study is: Is there an influence of internalizing Islamic values on the religious character of students at SMA Islam Kepanjen? Meanwhile, the objective is to analyze the influence of internalizing Islamic values on the religious character of students at SMA Islam Kepanjen. This study employed a quantitative approach with a correlational research design. Data collection techniques were carried out through questionnaires, documentation, and observation. The research sample was drawn from students using a non-probability sampling technique, specifically Accidental Sampling. Data were analyzed using normality tests, linearity tests, and simple linear regression analysis. The results of the regression analysis indicated a significance value of 0.001 < 0.05, meaning that there is a significant influence of Islamic internalization values on the religious character of students at SMA Islam Kepanjen. Furthermore, based on the results of the simple linear regression equation, the regression equation obtained is Y = 49.34 + 0.48X, which shows a positive relationship between Islamic internalization values and students' religious character. Consequently, the better the internalization process of Islamic values implemented, the higher the religious character of the students.